A longitudinal survey of business school graduates' assessments of business ethics - Arlow, Peter (Journal of business ethics, 1988)
A longitudinal survey of business graduates over a four-year period revealed stability over time in their assessments of proposals to improve business ethics except for significantly greater disapproval of government regulation. A comparison of graduates and executives indicate both favor developing general ethical business principles, business ethics courses, and codes of ethics, while disapproving government regulation and participation by religious leaders in ethical norms for business. The mean rankings by business graduates over time of factors influencing ethical conduct show significant declines in school-university training and significant increases for religious training and industry practices. Graduates and executives rank family training as the most important influence and school-university training as least important. The authors conclude that a more careful consideration be given to matching reform proposals and influence factors, and to increasing the depth of change efforts in individual business ethics.